ANALISIS SISTEM PENGARUH LALU LINTAS JALAN AKIBAT PEMBANGUNAN FLY OVER KERETA API BANTAIAN KABUPATEN MUARA ENIM - Rosyad, Farlin; Firdaus, Firdaus; Yoga Fradana, Muhammad (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The railroad crossing in Bantaian causes congestion, therefore it it is necessary to build a flyover in Bantaian. The purpose of this study was analyze the traffic performance of the Muara Enim road before the construction of the fly over was completed. The study used a survey method and road performance analysis based on MKJI 1997. The number of samples taken was 4 days on Monday, Tuesday, Wednesday, and Thursday. The results of the analysis of condition This research uses primary and secondary data. Primary data was obtained by taking traffic data on Monday 28 August 2023 to Thursday 31 August from 09.00 – 12.00 WIB and 12.00 – 18.00 WIB and secondary data in the form of data analysis in this research based on MKJI 1997. Based on the research that has been carried out, conclusions have been drawn. as follows, the highest vehicle volume value was obtained on Monday. The vehicle volume value on that day reached 3377 pcu/hour. Keywords: The results of the analysis of conditions during construction showed that the maximum degree of saturation on Monday morning from Muara Enim towards Prabumulih was 0.4717892 including the level of road service C, the maximum level of saturation on Monday morning from the direction of Prabumulih towards Muara Enim was 0.54 including the level of road service C, which was obtained based on traffic observations regarding the flyover constructionKeywords: mkji, capacity, vehicle flow, degree of saturation, and traffic performance